ChemInform Abstract: Facile Synthesis of 2‐Iodo‐spiro[indene‐1, 1′‐isobenzofuran]‐3′‐ones via Iodine‐Promoted Cascade Cyclization. Issue 8 (1st March 2013) - Zhu, Hai‐Tao; Dong, Xue; Wang, Li‐Jing; Zhong, Mei‐Jin; Liu, Xue‐Yuan; Liang, Yong‐Min
Abstract A novel method is elaborated for the synthesis of spiro derivatives (II) by iodine‐mediated cyclization of benzoates (I).